Motorcycle-related head and neck injuries: increased risk among ethnic minorities - Irit Cohen-Manheim; Irina Radomislensky; Maya Siman-Tov; Israel Trauma Group; Kobi Peleg (BMC, 2020)
Abstract Background Ethnic disparities have been associated with injury and mortality. The impact of ethnicity on head and neck injury (HNI), traumatic brain injury (TBI), in-hospital mortality and resource utilization following a motorcycle crash (MCC) is undetermined. This study explored the influence of ethnicity in these aspects and the effect of helmet use on HNI and TBI following a MCC. Methods The National Trauma Registry provided hospitalization data on motorcycle riders and passengers between 2008 and 2017. Ethnicity was classified as Jews or Arabs, the two major ethnic groups in Israel. Univariate followed by multivariable logistic models were applied to examine ethnic disparities. Mediation effect was tested by structural equation modeling. Results Among 6073 MCC casualties, Arabs had increased odds of HNI (OR = 1.37,95% CI = 1.12-1.65) and TBI (OR = 1.51,95%CI = 1.12-1.99), and a six-fold decreased odds of helmet use (OR = 0.16,95%CI = 0.12-0.22). The HNI and TBI associations with ethnicity were mediated by helmet use. Arabs had significantly higher odds for admission to intensive care unit (OR = 1.36,95%CI = 1.00-1.83), and lower odds for ambulance evacuation (OR = 0.73,95%CI = 0.61-0.89) and discharge to rehabilitation (OR = 0.55,95%CI = 0.39-0.7). In-hospital mortality was not associated with ethnicity. Conclusions Helmet non-use is an important etiologic factor associated with motorcycle-related HNI and TBI among Arabs. While in Israel, ethnic equality exists in in-hospital health care, disparities in ambulance and rehabilitation utilization was found. Intervention programs should target the Arab population and focus on helmet compliance.